TIGER BEETLES (COLEOPTERA: CARABIDAE: CICINDELINAE) OF COMPOSTELA VALLEY PROVINCE, MINDANAO ISLAND, PHILIPPINES - Milton Norman Dejadena Medina; Analyn Anzano Cabras; Jurgen Wiesner (SEAMEO BIOTROP, 2016)
The first faunistic record of tiger beetles (Coleoptera: Carabidae: Cicindelinae) in Compostela Valley Province, Mindanao with notes on their habitat is presented. Opportunistic sampling, standard light trapping and photo documentation were conducted in selected areas from January to April 2013 and in September 2015. One hundred four tiger beetles belonging to twelve species and seven genera were recorded. An astonishing (100%) endemicity was observed identified to subspecies level. Thopeutica and Calomera species, specifically Thopeutica anichtchenkoi Wiesner, 2015 and Calomera mindaoensis Cassola, 2000 were observed to be abundant in the samples mostly found in the mountainous and forested open riparian ecosystem of Cagan, New Bataan. Cylindera (Ifasina) discreta elaphroides (Dokhtouroff 1882) was the most common species and was found in different habitat types, but the majority of the species showed a narrow and specialized habitat preference. Protection and conservation of remaining forest areas in Cagan is especially important in preserving endemic species.